Politics, ethnicity and the postcolonial nation : a critical analysis of political discourse in the Caribbean - Esposito, Eleonora (Discourse approaches to politics, society, and culture, 2021)
"This book explores the politics of ethnicity and nationalism in the Caribbean from a critical discourse-analytical perspective. Focusing on political communication in Trinidad and Tobago, it offers unique socio-political insights into one of the most complex and diverse countries of the Archipelago. Through a detailed reconstruction of Kamla Persad-Bissessar's 2010 victorious run for office, this book offers ample empirical evidence of the multimodal discursive strategies that held the key to the success of the first woman PM candidate and her inter-ethnic coalition bid to overcome political tribalism in the country. In parallel, it explores the implications and challenges of the postcolonial Trinbagonian national project, caught between pluralism and creolization. Through its innovative, context-dependent and interdisciplinary CDS approach, this book breaks new ground in Caribbean Studies while at the same time broadening the horizons of the Euro-American tradition of Political Discourse Studies to address the complexities of global postcoloniality"--